2008
DOI: 10.2174/1875934300801010034
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Physical Workload and the Development of Musculoskeletal Symptoms Among Female Elderly-Care Workers

Abstract: Abstract:The aim of the present study was to investigate the relations between psychological and physical workload and musculoskeletal neck, shoulder and upper back symptoms. In this longitudinal two-phase cohort study a survey was conducted among non-managerial female elderly-care workers (n = 553). The analyses were based on respondents who were considered free from the respective symptoms at initial ratings, resulting in study samples of n = 230 for neck symptoms, n = 211 for shoulder symptoms, n = 400 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…In the present study, no indications of reversed causality were found. These results are contrary to a study among female child‐care workers where the psychosocial work environment was found to influence the risk of developing musculoskeletal pain, but where reversed causality was found in the total sample not distinguishing between pain processes (Larsman et al, 2007). In that study, more pain at baseline were related to higher perceived psychological workload at follow‐up, suggesting that although aspects of the psychosocial work environment are important for the development of musculoskeletal pain, such factors may be of less importance for other processes such as maintenance or recovery from pain (Larsman et al, 2007).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, no indications of reversed causality were found. These results are contrary to a study among female child‐care workers where the psychosocial work environment was found to influence the risk of developing musculoskeletal pain, but where reversed causality was found in the total sample not distinguishing between pain processes (Larsman et al, 2007). In that study, more pain at baseline were related to higher perceived psychological workload at follow‐up, suggesting that although aspects of the psychosocial work environment are important for the development of musculoskeletal pain, such factors may be of less importance for other processes such as maintenance or recovery from pain (Larsman et al, 2007).…”
Section: Discussioncontrasting
confidence: 99%
“…Previous research on risk factors for musculoskeletal pain indicates that there may be different risk factors related to the incidence, recurrence, persistence of and recovery from pain (Larsman, Pousette, & Johansson Hanse, 2007; Luime et al, 2004). The present study focused on the development/recurrence of pain, and therefore, only those participants reporting no pain at the first measurement occasion were included in the analyses.…”
Section: Introductionmentioning
confidence: 99%
“…These partly contradictory results on synergetic effects among health and care employees reflect inconsistencies in previous research on these occupations, as well as on other occupations. Additive interaction effects of physical and psychosocial job factors on absenteeism or disability were reported in some studies [ 10 , 11 , 12 , 13 , 20 , 28 ], while a number of other studies found no additive interaction effects of such combined exposures on sickness absence [ 22 , 23 , 25 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study of hospital employees demonstrated that simultaneous exposure to emotional demands, time pressure, and cognitive demands had an additive disadvantageous effect on sleep, exhaustion, and job satisfaction [ 26 ], and a study by our research team found additive interaction effects between combined physical and psychosocial exposures and future disability pension among Swedish health and care workers [ 28 ]. However, no interaction effect was found between psychological and mechanical workloads and musculoskeletal symptoms in a study of female childcare workers in Sweden [ 37 ]. Despite the fact that health and care workers often report simultaneous exposure to physical and psychosocial risks, no study has been found on the interaction effects of physical and psychosocial exposures on sickness absence.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, workers get workload both physically and mentally. Mental workload have a more significant relations with the musculoskeletal problem (neck and upper back) [11]. Mental workload consisting of some factors that influence the worker's mental processing of information, decision making process and individual reactions [12].…”
Section: Introductionmentioning
confidence: 99%